2020
DOI: 10.3390/ijerph17197225
|View full text |Cite
|
Sign up to set email alerts
|

The Removal of Residual Concentration of Hazardous Metals in Wastewater from a Neutralization Station Using Biosorbent—A Case Study Company Gutra, Czech Republic

Abstract: This article deals with the possibility of using a biosorbent in the form of a mixture of cones from coniferous trees to remove the residual concentration of hazardous metals contained in hazardous waste, which is disposed of in a neutralization station. The efficiency of the tested biosorbent in removing Ni, Zn, Cu, and Fe was monitored here. Laboratory research was carried out before the actual testing of the biosorbent directly in the operation of the neutralization station. With regard to the planned use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 39 publications
(23 reference statements)
0
10
0
Order By: Relevance
“…The authors determined that the tested material (Saccharomyces cerevisiae) can be considered an effective, cheap and efficient sorbent for the treatment of complex effluents, particularly nickel ion removal. Pertile et al (2020) investigated the possibility of using a biosorbent which is a mixture of cones from coniferous trees to remove the residual concentration of metals from hazardous waste at a neutralization station. In their work, they presented both preliminary studies performed in laboratory conditions and tests from the operation of the neutralization station.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors determined that the tested material (Saccharomyces cerevisiae) can be considered an effective, cheap and efficient sorbent for the treatment of complex effluents, particularly nickel ion removal. Pertile et al (2020) investigated the possibility of using a biosorbent which is a mixture of cones from coniferous trees to remove the residual concentration of metals from hazardous waste at a neutralization station. In their work, they presented both preliminary studies performed in laboratory conditions and tests from the operation of the neutralization station.…”
Section: Discussionmentioning
confidence: 99%
“…For nickel sorption, both plant parts such as bark (Cancelo-Gonza ´lez et al 2017;Akar et al 2019) or cones (Oguz 2020), and more fragmented parts such as fibers (Boudaoud et al 2017), bagasse (Rico et al 2018;Candelaria et al 2019) and sawdust (Richard et al 2020) were used. Researchers have also used algae (Vetrivel et al 2017;Kipigroch 2018; El-Naggar and Rabei 2020) and fruits (Pertile et al 2020) including their seeds (Aravind et al 2017), shells (Cruz-Lopes et al 2021 or peels (Priyantha and Kotabewatta 2019) to remove metals from aqueous solutions. The least amount of research was observed for the organisms category containing materials from invertebrates, insects, and their shells (Gu ¨rel and Gu ¨nes ¸2018; Foroutan et al 2019;Marzuki et al 2019;Złotko et al 2021).…”
Section: Trends In Biosorbent Researchmentioning
confidence: 99%
“…In contrast, anions present in salt solutions: HCO 3 − , CO 3 2− , Cl − , and SO 4 2− , can destabilize the biosorbent-metal complex and capture bound metal ions to form complexes with them [114,115]. A complexing agent such as EDTA can also be used for the desorption process, which forms a stable complex with heavy metal ions, being a competitor to the sorbent [116,117]. It is important to use a suitable desorbent, which, on the one hand, will be efficient and on the other hand, will not damage the surface of the biosorbent which will allow its reuse.…”
Section: Desorption Of Biosorbentmentioning
confidence: 99%
“…After one day of contact between wastewater and biosorbent, the concentrations of Cu, Ni, Zn, and Fe decreased from 2252, 4056, 4020, and 1853 mg/L to 13, 24, 18, and 28 mg/L, respectively. Based on the research, the cones of coniferous trees' mixture were found to be suitable for treatment with a total of 10,000 L of galvanic process wastewater [116]. In the study of Aimal et al peels of different fruits such as orange, watermelon, mango etc., were used as biosorbent for metal removal.…”
Section: Application Of Biosorbents and Perspectivesmentioning
confidence: 99%
“…Conventional treatment methods that involve an integration of physical, chemical, and/or biological processes, such as chemical precipitation, flocculation, and reverse osmosis, have been previously considered as sustainable waste management, but ultimately proved inefficient (Azimi et al 2017). Several drawbacks include high costs, long processing time, and the generation of excess sludge that require further disposal (Pertile et al 2020). Thus, it is imperative to develop an environmentally friendly, cost effective, and efficient method to maintain ecosystem health.…”
Section: Introductionmentioning
confidence: 99%